2014
DOI: 10.1002/pip.2473
|View full text |Cite
|
Sign up to set email alerts
|

Secondary phase formation in Zn‐rich Cu2ZnSnSe4‐based solar cells annealed in low pressure and temperature conditions

Abstract: Zn‐rich Cu2ZnSnSe4 (CZTSe) films were prepared by a two‐step process consisting in the DC‐magnetron sputtering deposition of a metallic stack precursor followed by a reactive anneal under a Se + Sn containing atmosphere. Precursor composition and annealing temperature were varied in order to analyze their effects on the morphological, structural, and optoelectronic properties of the films and solar cell devices. Raman scattering measurements show the presence of ZnSe as the main secondary phase in the films, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
109
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 24 publications
17
109
1
2
Order By: Relevance
“…Many studies have also reported void formation in CZTSe due to Sn reaction and movement. 19 The obtained result is in accord with reports from Ge et al, 11 which showed that CZTS was converted to CZTIS, and a SnO 2 interlayer between CZTIS and ITO was observed as a result of In diffusion. However, in this work, the ITO was completely converted to SnO 2 .…”
supporting
confidence: 92%
“…Many studies have also reported void formation in CZTSe due to Sn reaction and movement. 19 The obtained result is in accord with reports from Ge et al, 11 which showed that CZTS was converted to CZTIS, and a SnO 2 interlayer between CZTIS and ITO was observed as a result of In diffusion. However, in this work, the ITO was completely converted to SnO 2 .…”
supporting
confidence: 92%
“…[19,34]. The effects of the back contact degradation after selenization can be clearly observed in Figure S1 of the Supporting information (S.I.…”
Section: Methodsmentioning
confidence: 95%
“…Nevertheless, secondary phases with overlapping peaks such as Cu 2 Sn(S,Se) 3 and Zn(S,Se) could occur too. [ 19 ] The main CZTSSe peaks are attributed to the A 1 vibration mode of S (Z2′-Z6′: 191, 202, 213, 216, 233 cm −1 ) and Se atoms (Z2′-Z6′: 322, 324, 325, 325, 329 cm −1 ) surrounding the cations. [ 38 ] The peak shift is due to the increased vibrational frequency resulting from lighter S atoms and CZTSSe with intermediate S/(S + Se) ratio exhibits a bimodal behavior.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…[ 16 ] On the formation of CZTSe, SnSe was found at the back interface while ZnSe was found both on the surface (Zn/ Sn = 1.24 and annealing temperature < 500 °C) and back interface (Zn/Sn = 1.73) depending on the processing condition. [ 19 ] Therefore, secondary phase formation and segregation might be expected to be process dependent. The above reviews show that secondary phases typically coexist and impact the electrical behavior, especially in pure-sulfi de CZTS.…”
Section: Introductionmentioning
confidence: 99%